2001
DOI: 10.1192/bjp.179.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behaviour in patients with schizophrenia is associated with catechol-O-methyltransferase genotype

Abstract: The high-activity homozygotes showed significantly higher scores of aggression, whereas the heterozygotes showed significantly lower scores. The odds ratio for aggression for the high-activity homozygotes was 2.07 (95% Cl=1.03-4.15), whereas that for the heterozygotes was 0.54 (95% Cl=0.30-1.00). CONCLUSIONS; The high-activity COMT homozygote confers a higher risk of recorded aggression in schizophrenia. Heterozygotes had a significantly lower risk, which may represent an example of heterosis/heterozygote adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
2
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 12 publications
4
55
2
5
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20][21][22][23] Of these, eight had adopted a prospective longitudinal study design, 12,14,15,18,19,[21][22][23] three were case-control studies 16,17,20 and one was a transversal study. Six studies related aggressive behavior to genic expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[12][13][14][15][16][17][18][19][20][21][22][23] Of these, eight had adopted a prospective longitudinal study design, 12,14,15,18,19,[21][22][23] three were case-control studies 16,17,20 and one was a transversal study. Six studies related aggressive behavior to genic expression.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies related aggressive behavior to genic expression. [12][13][14][15][16][17] Two demonstrated the genic expression of the serotonin transporter, 13,14 one demonstrated the genic expression of the monoaminaoxidase (MAOA), 12 another study demonstrated the genic expression of the transporter and the receptor of dopamine, 15 and two studies presented the genic expression of the catechol-O-methyltransferase enzyme (COMT). 16,17 Four studies related aggressive behavior to maternal exposure to psychoactive substances.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methionine allele has been associated with aggression, suicide, worse prognosis and greater positive symptom severity in schizophrenia. 91,[96][97][98][99][100] Egan et al's finding of an association between the valine allele and poor WCST performance has generated renewed interest in this area of investigation, especially with regard to the effects of COMT in mediating cognition in schizophrenia. 52 This finding has been replicated in part by Joober et al, who found that genotype effects on WCST performance among schizophrenia patients was at a trend level of significance, and was nonsignificant in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%